2018–2019 Florida Citrus Production Guide: Citrus Under Protective Screen (CUPS) Production Systems - Arnold W. Schumann; Ariel Singerman; Alan L. Wright; Rhuanito S. Ferrarezi (EDIS)
This 2-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. This summary of concepts, progress, and tentative recommendations from the first three years of CUPS research in Florida was condensed from a comprehensive CUPS Quick Start Guide that will be published and updated on the UF/IFAS EDIS website. Written by A. W. Schumann, A. Singerman, A. L. Wright, and R. S. Ferrarezi, and published by the Horticultural Sciences Department, January 2019.